ChemInform Abstract: Rhodium‐Rich Germanides RERh4Ge2 (RE: Y, Gd—Lu): Structure and Bonding. Issue 44 (15th October 2015) - Vosswinkel, Daniel; Matar, Samir F.; Poettgen, Rainer
Abstract The title compounds are prepared by arc‐melting of the elements and subsequent annealing (evacuated silica tube, 970 K, 5d).